DEPOSIT INSURANCE 101 : The Essentials We Need to Know - Sharifah Adlina Syed Abdullah, (2022)
This book is to help understand the basics of deposit insurance.DEPOSIT INSURANCE 101 : The Essentials We Need to Know is a book packed with funfilled facts about deposit insurance. It would be imperative for you to know how deposit insurance works in protecting your deposits in the banks. This understanding will help you to avoid panic behaviour to withdraw your deposits unnecessarily if there are rumours about the state of health of your banks. In actuality your deposit insurer or government; so you do not need to rush to the bank and be in the long queue in the first place. As much as I would say there is one design feature of deposit insurance that fits all, however this is not the case. As we live in different countries, our government's policy decisions on deposit insurance differ. This book helps you to be aware of the main design features of deposit insurance. By knowing some of these design features it will help you to plan and making an informed decision to ensure safety of ypurdeposits in the banks. For instance, you must know where to put your money and in how many accounts or banks you should put them to secure full protection of your hard-earned savings.